Arctic Portal - Jóhannsson, Halldór (Arctic Portal, 2011)
Mr. Halldór Jóhannsson from Arctic Portal, Akureyri, Iceland, introduces Arctic Portal when he talks here in the NRF 6th open assembly in Hveragerði, Iceland, in September of 2011. Please click on the link above to see the video.